Correction: DBU-catalyzed biobased poly(ethylene 2, 5-furandicarboxylate) polyester with rapid melt crystallization: synthesis, crystallization kinetics and melting behavior. Issue 23 (1st March 2017) - Wu, Jiaping; Xie, Hongzhou; Wu, Linbo; Li, Bo-Geng; Dubois, Philippe
Abstract : Correction for 'DBU-catalyzed biobased poly(ethylene 2, 5-furandicarboxylate) polyester with rapid melt crystallization: synthesis, crystallization kinetics and melting behavior' by Jiaping Wu et al., RSC Adv., 2016, 6, 101578–101586.